MAKNA HEURISTIK DAN HERMENEUTIK DALAM PAPPASANG MASYARAKAT MAKASSAR (TINJAUAN SEMIOTIKA RIFFATERRE) - Syamsurya, Nuraliyah; Hajrah, Hajrah; Asia M, Asia M (Journal Studies in Indonesian Language and Literature, 2024)
The title of this research is “The Meaning of Heuristics and Hermeneutics in The Pappasang of Makassar Society (Review of Riffaterre Semiotics)”. This study aims to reveal the heuristic and hermeneutic meaning in Makassar community pappasang. The research method used in this study is descriptive qualitative. The results of this study indicate that the pappasang of the Makassar community analyzed from the book Pasang and Paruntuk Kana in Classical Makassar Literature found words or sentences in the expression of pappasang all indicated heuristic and hermeneutic meanings. Heuristic meaning is the first level of reading based on reading language conventions by finding the nuances of language meaning contained in a pappasang and in it are found things related to the phenomena of individual life which include religion, morals and social, hard work and unity, sirik na pacce, and leadership. Hermeneutic meaning is the second level of reading based on reading literary conventions that provide interpretations of the meaning contained in the pappasang and reveal more of the intent of the contents of the pappasang.